The role of media and community engagement in COVID-19 vaccinations in Tanzania - Ambrose T. Kessy; Chima E. Onuekwe; William M. Mwengee; Haonga Tumaini (Journal of Public Health in Africa)
Background: The COVID-19 pandemic underscored the critical role of communication strategies in influencing public health behaviours, particularly vaccine uptake. In Tanzania, media and community engagement strategies have been pivotal in efforts to enhance COVID-19 vaccine acceptance; however, their effectiveness remains under scrutiny.